Little Tim and the brave sea captain - Ardizzone, Edward 1900-1979 (Oxford University Press, 1936)
Follows the adventures of a stowaway boy, including his friendship with captain and crew and near shipwreck during a violent storm
"Lithographed in the U.S.A.". - Text is hand-lettered. - Publisher's advertisements on dust jacket
Keywords: Seafaring life / Juvenile fiction; Sailors / Juvenile fiction; Ship captains / Juvenile fiction; Stowaways / Juvenile fiction; Courage / Juvenile fiction; Rescues / Juvenile fiction; Voyages and travels; Sea stories; Children's literature / Picture-books; Schiff; Junge; Meer; Bilderbuch; Abenteuer; Kapitän